Developing an Augmented Reality Application as Instruction Media to Help in Learning the Solar System - Muhammad Sholeh; Erfanti Fatkhiyah; Heru Aprianto (Indonesian Scientific Journal, 2023)
This study aimed to develop an application to help in learning the solar system using Augmented Reality (AR) technology. In an era where technology is very developed, learning about the solar system can be made more interactive by providing 3D illustrations to the students. One of the technologies that can be applied to support the development of educational applications to help in learning about the solar system is AR technology. It can create 3D illustrations. The study is the Research and Development (R&D). The research produced an AR-based solar system introduction application. This application can be used as a learning media for students. The developed AR application was tested using alpha and beta testing. The alpha testing was the marker accuracy testing and black-box testing, while the beta testing was done by distributing questionnaires to 30 respondents and then doing validity and reliability test. This study produced an AR application to help in learning the solar system. The black-box testing showed that the AR application generally was functioning well. The marker accuracy testing showed that the AR camera succeeded in scanning markers up to 25% of the marker area. The data obtained from distributing questionnaires were processed to know the validity in terms of attractiveness and effectiveness, and the results showed the data was valid. Moreover, the reliability testing was carried out with Cronbach's alpha, and the result was 0.771 for the attractiveness aspect and 0.742 for the effectiveness aspect. These values mean that most beta testers agree that the AR application was attractive and effective.